Changes in public awareness of racial, economic, and educational health disparities between 2007 and 2023 among Wisconsin adults - Stephanie A. Robert; Amy Yinan Liu (Preventive Medicine Reports)
Objective: To investigate 15-year changes in public awareness of racial, economic, and educational health disparities between 2007 and 2023. Methods: Surveys of Wisconsin, U.S. adults in 2007 and 2023 were compared. Respondents in both surveys were randomized into panels to examine opinions about specific health disparities—Black/White, economic, or educational health disparities. Bivariate and logistic regression analyses examine how demographic factors differentiate awareness of disparities and changes in awareness over 15 years. Results: Overall awareness of Black/White and educational health disparities rose between 2007 and 2023; awareness of economic health disparities remained at a similar high level both years. Despite overall increases in awareness of health disparities, some demographic differences in awareness persisted between years by age, gender, race, education, and party identification. There are particularly large differences between Republicans and Democrats in awareness of each type of health disparity. The increase in awareness of Black/White health disparities grew much faster over 15 years for Democrats than Republicans. Conclusions: The overall increase in awareness of health disparities is encouraging if improvement in public awareness helps drive initiatives to address the disparities. However, the large and even growing political divide on health disparity awareness is concerning and our results support calls for deep attention to how to bridge huge partisan divides in understanding and addressing health disparities to improve health and health equity in the U.S.